Effect of Method Aerobic Circuit Training on Speed, Power and Aerobic Capacity of Athletes Softball - Haryono, Tono; Agus Rusdiana; Angga M Syahid; Iwa Ikhwan Hidayat; Kurniawan, Tian; Didin Budiman; M Naufal Abdurahman (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2024)
This study aimed to determine the impact of aerobic circuit training on increasing anaerobic capacity, specifically focusing on movement speed, strength, and aerobic capacity. The method used to obtain data and achieve the objectives was an experimental method, employing a one-group pretest-posttest design by providing treatment to students from the Softball Student Activity Unit at the Indonesian Education University. The results of the study showed that (1) carrying out the exercise did not have a significant impact on increasing anaerobic dynamic capacity, (1.a) carrying out the exercise had a significant impact on increasing movement speed ability, (1.b) carrying out aerobic circuit training did not have a significant impact on increasing power capacity, and (2) the implementation of aerobic circuit training had a significant impact on increasing dynamic aerobic capacity.